Gender, sexual discourse, and women's pleasure in later medieval England, c.1300-c.1550 - Raw, A (2023)
This thesis brings multiple methodologies together to examine where we might find pleasure and sexual subjectivity for women in later medieval England. At once working to uncover the assumptions within historians’ theoretical frames and lay new groundwork, in the Introduction I explore the semantic and theoretical challenges, and propose some new methods, focussing on pleasure as an operative term.